2003
DOI: 10.1073/pnas.0830856100
|View full text |Cite
|
Sign up to set email alerts
|

An empty Drosophila stem cell niche reactivates the proliferation of ectopic cells

Abstract: Stem cells are thought to reside in regulatory microenvironments (“niches”) generated by stable stromal neighbors. To investigate the significance of empty niches vacated by stem cell loss, we studied Drosophila ovarioles, which maintain two to three germ-line stem cells in a niche requiring adhesive stromal cap cells and Decapentaplegic signals. After experimentally emptying the germ-line stem cell niche, cap cell activity persists for several weeks. Initially, somatic inner germarium sheath cells enter the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
216
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 255 publications
(233 citation statements)
references
References 27 publications
14
216
0
Order By: Relevance
“…The formation of GSC tumors in response to bab1-Gal4-driven expression of dpp in anterior somatic cells, the likely source of BMP ligands in the GSC niche, suggests that the levels of BMP/Dpp ligand are an essential limiting factor in the normal restriction of GSC maintenance to those cells in contact with the CpC cells. In this regard, we note that dpp expression primarily from somatic cells within region 2 of the germaria also induces similar GSC tumors (Kai and Spradling, 2003;Zhu and Xie, 2003;Song et al, 2004), suggesting that GSC tumor phenotypes are sensitive to the availability, but not to the pattern, of ligand expression within the germarium.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The formation of GSC tumors in response to bab1-Gal4-driven expression of dpp in anterior somatic cells, the likely source of BMP ligands in the GSC niche, suggests that the levels of BMP/Dpp ligand are an essential limiting factor in the normal restriction of GSC maintenance to those cells in contact with the CpC cells. In this regard, we note that dpp expression primarily from somatic cells within region 2 of the germaria also induces similar GSC tumors (Kai and Spradling, 2003;Zhu and Xie, 2003;Song et al, 2004), suggesting that GSC tumor phenotypes are sensitive to the availability, but not to the pattern, of ligand expression within the germarium.…”
Section: Discussionmentioning
confidence: 77%
“…2C), we thought that bab1-Gal4 might be useful for the ectopic expression of ligands in the stromal CpCs, TFCs, and IGS cells. To test this, we wanted to determine if bab1-Gal4-mediated expression of dpp could induce hyperplastic GSC growth, characterized by the presence of hundreds of spherical spectrosome containing GSC-like cells, which has previously been observed when dpp was expressed in FCs and IGS cells (Kai and Spradling, 2003;Zhu and Xie, 2003;Song et al, 2004;Xi et al, 2005). However, we found that ectopic expression of dpp when driven by bab1-Gal4 was lethal (data not shown).…”
Section: Genetic Dissection Of Signaling Mechanisms Responsible For Gmentioning
confidence: 87%
See 2 more Smart Citations
“…The latter hypothetical scenario, if proven, illustrates an exciting new possibility for the limbal niche in directing trafficking and homing of host circulating SCs, an emerging concept well documented in the hematopoietic niche (for review, see [102]), and the Drosophila germline niche [103].…”
Section: Will Restoration Of Niche Support Be Critical For Ex Vivo Exmentioning
confidence: 93%